Analyze Potential And Mitigate Business Risks For Women Entrepreneurs - Teti Rahmawati; Dendi Purnama; Neni Nurhayati (EQUATOR SINAR AKADEMIA, 2023)
Kuningan Regency is ranked 19th for the number of MSMEs in each district. So, it must continue to be pursued to increase public interest in starting a business. We strive to be involved in assisting the community to improve the economy through assistance to the community for fostering entrepreneurial spirit, financial planning, and managing potential business risks. With the application of a measurable understanding of potential risks and mastering how to mitigate risks before starting a business, it is hoped to increase the enthusiasm of community members to start a business and succeed in running their business. Especially for PKK mothers and female heads of households as training participants plus youth organizations. This service activity aims to provide knowledge to understand and analyze potential business risks and improve the ability to mitigate business risks in the morning for prospective women entrepreneurs and youth organizations in Gandasoli Village. From the evaluation results, it was found that out of 37 participants, most of them understood the meaning of risk and the types of risks that could potentially arise when they would carry out business activities. Participants have also been able to identify the risks of the business plan that they will do.